THE RELATIONSHIP BETWEEN CYBERBULLYING AND STRES LEVELS IN UNIVERSITY STUDENTS - Adelia Dwi Mareta; Wita Oktaviana Wita (Fakultas Kedokteran Universitas Sriwijaya, 2026)
The Relationship between Cyberbullying and Stres Level on Students. Children are at that stage of development when they can be pressured. If that pressure becomes more than they can bear, it can lead to stres. There's no alternative for students to social media as a means of self-development. Excessive use of social media can also result in cyberbulling. The purpose of this study was to find out the relationship between cyber bullying with stres on health student students in Faculty of Health Science University Muhammadiyah Surakarta. Design and methods: This research utilised a quantitative correlational cross-sectional design. A total of 129 respondents were sampled using purposive sampling. Data were collected through questionnaires consisting of the Cyberbullying and Online Aggression Survey with a validity of (0.436-0.928) and the Perceived Stres Scale (PSS-10) questionnaire with a Cronbach's alpha of (0.81). The data were analysed using Spearman's Rho test. The findings indicate an association between cyberbullying victimisation and the school-related stres of students (p-value = 0.001) as well as a relationship between cyberbullying behavior and school-related student stres (p-value = 0.003). This line of research should generate insight into the effects of cyberbullying on stres.